THE EFFECTS OF CYLINDRICAL HOLE ON NATURAL FREQUENCY OF COMPOSITE THICK PLATE - Yesil, Uslku Babuscu (YILDIZ TECHNICAL UNIV, 2009)
In this study, the effects of cylindrical hole on natural frequency of composite thick plate are considered. Mathematical modelling of the problem is made by helping of the three dimensional motion equation of linear elasticity theory. The solution of the problem is made numerically using three dimensional finite elements method. The effect of cylindrical hole on dynamical behavior of considered thick plate is investigated with different geometric and material parameters.
Keywords: Composite thick plate; natural frequency; cylindrical hole; finite elements method; FREE-VIBRATION; Engineering